MEROKOK DI KALANGAN MAHASISWA (STUDI KASUS FAKULTAS KEDOKTERAN UNIVERSITAS RIAU) - Putri Meilani; Tengku Romi Marnally (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Smoking can increase death risk from many types of cancers (ec : lung cancer), heart stroke, throat inflammation, and pregnancy disease. Students of Medical Faculty of Riau University have capability and good knowledge about health and the smoking effect. But from the research showed that there were several of them smoking. This research used qualitative method with descriptive approach. Informans in this research were the smoking students of Medical Faculty of Riau University with total 5 respondents. Accumulation of data, observation, and the collected data was explained as qualitative. The economic social background of informans was from high-status family which it made them bought cigarettes easily. The result showed that family and friends had relation with smoking attitude. But the informans said friends were main factor. Personal factor also influenced them to smoke, and they said smoking could make disappear their bored and daily problems.Keywords : student of medical faculty, smoking activity, smoking factor.